Meningkatkan Aktivitas Dan Hasil Belajar Siswa Pada Pembelajaran Ipa Melalui Penggunaan Multimedia Di Kelas Iii Sdn Model Terpadu Madani - Hikmah Tomodu (Mitra Sains, 2017)
This research aimed to find out the effect of using multimedia toward the students’ learning outcomes. The research method used research class treatment (PTK) Kemmis and Mc. Taggart model. The subject of this research was 20 students of third grade of SDN Model Terpadu Madani, by different abilities. The result show that the students activities at science instruction at science instruction in nature conservation lessons. It was known by the improving learning activities of the students carried out well. Learning outcomes of the students at Grade III SDN Model Terpadu Madani on Natural Science got improvement. Pre-treatment did not get the classical learning mastery that was decided in cycle 1 got improvement but did not get learning mastery that was decided. Improvement activities and learning outcomes were effect from learning involved teacher activities constructively with skills and abilities to operated multimedia through infocus.